Sarcopenia predicts readmission and mortality in elderly patients in acute care wards: a prospective study. Issue 2 (28th November 2016) - Yang, Ming; Hu, Xiaoyi; Wang, Haozhong; Zhang, Lei; Hao, Qiukui; Dong, Birong
Abstract: Background: The aim of this study is to assess the prevalence of sarcopenia and investigate the associations between sarcopenia and long‐term mortality and readmission in a population of elderly inpatients in acute care wards. Methods: We conducted a prospective observational study in the acute care wards of a teaching hospital in western China. The muscle mass was estimated according to a previously validated anthropometric equation. Handgrip strength was measured with a handheld dynamometer, and physical performance was measured via a 4 m walking test. Sarcopenia was defined according to the recommended diagnostic algorithm of the Asia Working Group for Sarcopenia. The survival status and readmission information were obtained via telephone interviews at 12, 24, and 36 months during the 3 year follow‐up period following the baseline investigation. Results: Two hundred and eighty‐eight participants (mean age: 81.1 ± 6.6 years) were included. Forty‐nine participants (17.0%) were identified as having sarcopenia. This condition was similar in men and women (16.9% vs. 17.5%, respectively, P  = 0.915). During the 3 year follow‐up period, 49 men (22.7%) and 9 women (16.4%) died ( P  = 0.307). The mortality of sarcopenic participants was significantly increased compared with non‐sarcopenic participants (40.8% vs. 17.1%, respectively, P  < 0.001). After adjusting for age, sex and other confounders, sarcopenia was an independent predictor of 3 year mortality (adjusted hazard ratio: 2.49; 95% confidential interval: 1.25–4.95) and readmission (adjusted hazard ratio: 1.81; 95% confidential interval: 1.17–2.80). Conclusions: Sarcopenia, which is evaluated by a combination of anthropometric measures, gait speed, and handgrip strength, is valuable to predict hospital readmission and long‐term mortality in elderly patients in acute care wards.